Constructing a successful career in the Fourth Industrial Revolution for young graduates in the UAE - AHMED, AYMAN MOUSTAFA HANAFY (2022)
A lifetime career, job security, promotions, and career development in one organization are no longer guaranteed for young graduates. Today, during the fourth industrial revolution, career ambiguity and rapid changes in the nature of work have presented young graduates with many challenges in constructing their careers. For example, globalization, advances in technology, the COVID-19 pandemic, and the trend towards more information and service-based business have required individuals to have a clear career path and to be adaptable, flexible, and proactive in their career behavior. In recent years, and particularly during the COVID-19 pandemic, young graduates have found it increasingly difficult to secure full-time employment with career prospects, and many individuals have begun questioning the meaning of their jobs and careers (Baruch and Sullivan, 2022; Duffy et al., 2016; Trevor-Roberts et al., 2018). Due to technological advancements, economic changes, and global competition, individuals often have to change employer or retrain for a new career. To respond to changing labor market needs and job opportunities, individuals need to carefully plan and manage their career development, improving both their career competencies and commitment. Career competencies have become important in today’s labor markets (Kong et al., 2012), so that individuals can obtain, retain, and effectively manage their careers (Heijde and Van Der Heijden, 2006). Employees worldwide are experiencing uncontrollable job losses and career interruptions (Ng et al., 2005). Accordingly, individuals are required to pay high attention to managing and shaping their careers to address the complex and unpredictable changes in business. Akkermans et al. (2012) identified three categories of career competencies – namely reflective, communicative and behavioral – which reflect the four perspectives of boundaryless career, protean career, career self-management, and human capital. Few studies have examined the effects of boundaryless and protean career competencies components on young graduates’ subjective career success. To our knowledge, only Eby et al. (2003) have investigated the impact of boundaryless career competencies on young graduates, while other studies investigated boundaryless career competencies in general, with less emphasize on specifying which component significantly impacts career success (e.g., Akkermans and Tims, 2017; Blokker et al., 2019; Cappellen and Janssens 2008; Francis-Smythe et al., 2013; Kuijpers et al., 2006; Park, 2020). To our knowledge, no study has examined the effects of protean career competencies components on young graduates’ career success. Additionally, all the research that has investigated the impacts of career commitment (career planning, career resilience, and career identity) on career success are general and did not specify which component of career commitment has the superior impact on career success (Ballout, 2009; Carson et al., 1999; Day and Allen, 2004; Karavardar, 2014; Najam et al., 2020; Poon, 2004; Sultana et al., 2016). This research aims to assess the significant impacts of the different components of career competencies and career commitment on young graduates’ career success, and how these individuals construct their careers in the fourth industrial revolution. Thus, the study seeks to answer the following research questions: • To what extent do career competencies impact upon the career success of young graduates in the fourth industrial revolution? • To what extent does career commitment impact upon career success of young graduates in the fourth industrial revolution? • How do young graduates build successful careers during the fourth industrial revolution? The study adopted a quantitative, deductive, cross-sectional research method to explain how young graduates in the United Arab Emirates (UAE) construct their successful careers in the fourth industrial revolution. To our knowledge, this is the first study to investigate the combined impacts of career competencies and career commitment components on recent graduate career success. This research contributes to boundaryless career, protean career, and career construction theory, by improving our understanding of the role of the various components within the related constructs. In addition, it addresses a recent call for more research that investigates aspects of job crafting, whereby individuals make changes to their jobs or job roles to make better use of their skills and abilities and to ensure their career development (Tims et al., 2022). By examining the impacts of career competencies and career commitment components on subjective career success, the study also makes a useful contribution to the career success literature, which contains considerable ambiguity and contradictions. Since existing studies were mostly undertaken in Western countries, this study, which was conducted in an Arab Gulf/Middle Eastern context, allows us to account for the possible influences of economic, political and social factors, such as culture and religion, as well as the composition of labor forces in this region (there are very high proportions of expatriate labor in some Arab Gulf countries).